Generation of two genomic-integration-free DMD iPSC lines with mutations affecting all dystrophin isoforms and potentially amenable to exon-skipping - Ferrari, Giulia (Stem Cell Res, 2020)
Duchenne muscular dystrophy (DMD) is the most common paediatric muscular dystrophy and is caused by mutations in the DYSTROPHIN gene. We generated two induced pluripotent stem cell (iPSC) lines from DMD patients with nonsense mutations in exons 68 (UCLi011-A) or 70 (UCLi012-A) by transfecting reprogramming mRNAs. Both mutations affect expression of all dystrophin isoforms. iPSCs expressed pluripotency-associated markers, differentiated into cells of the three germ layers in vitro and had normal karyotypes. The selected mutations are potentially amenable to read-through therapies, exon-skipping and gene-editing. These new iPSCs are also relevant to study DYSTROPHIN role in tissues other than skeletal muscle.